Decrease of external skeletal robustness (Frame index) between two cohorts of school children living in Puerto Madryn, Argentina at the beginning of the 21st century - Navazo, Bárbara (2020)
Background: It has been shown that modern life style with reduced physical activity can lead to lower bone accumulation. Also a decline trend in external skeletal robustness in children and young adolescents, measured by the Frame Index (FI), seems to have a parallel trend with the increase in overweight and obesity. Based on these findings we estimate that likely, the FI should be changed after a decade in the Argentinean population as well as in others population of the world. Thereby, the aim of the present study was to describe, using the FI, the pattern of external skeletal robustness in school children aged 6–14 years from two cohorts of Argentina (Puerto Madryn, Chubut) and to compare them with the European reference (Czech Republic, Germany, Poland and Russia). Methods: Elbow breadth and height of Puerto Madryn school children were collected in two cross-sectional studies conducted between 2001–2006 (cohort 1 = C1) and 2014– 2016 (cohort 2 = C2). Percentiles (P) values, for males and females, from C1 and C2 were calculated combining the LMS-method and its extension. A t-test has been used to compare, by age and sex, the FI values between the Argentinean cohorts and the European reference (ER). Then, in order to know the percentage of the variation of the percentiles values between cohorts, as well as with ER, percent differences between means (PDM%) were employed. Results: FI from Argentinean cohorts differed significantly from ER. Even more, C2 was not only smaller than ER, but also than C1. In males, C1-C2 showed significant differences at 6–8, 11 and 12 years and in females at all ages. Then, respect to ER each Argentinean cohort showed significant differences in males of C1 at 6, 12–14 years and in females at 6 and 11–14 years; and of C2, in both sexes, from 6 to 14 years. The PDM% values for elbow breadth of male were negative in ER-C1 in all percentiles analyzed; in ER-C2 positive (P3 and P50) and negative (P97) and C1-C2 recorded positive values. In females, elbow breadth showed negative values for ER-C1 (P50 and P97), and positive for the remaining values. Finally, height registered, in both sexes, negative values in ER-C1 (except P97 in females), ER-C2 and C1-C2. Conclusions: After ten years of the first study carried on in Puerto Madryn, school children show a negative trend in the external skeletal robustness. Additionally, the children of both Argentinean cohorts have lower values compared to the European reference, and mainly the actual cohort. This situation would be explained, in part, by the progressive increase over time of overweight and obesity as consequence, among others, of the change in the quantity and/or quality of the food that children have access to and with the physical activity they do at school and outside.